Predictors and Outcomes of Heart Failure With Preserved Ejection Fraction in Patients With a Left Ventricular Ejection Fraction Above or Below 60% - Akito Nakagawa; Yoshio Yasumura; Chikako Yoshida; Takahiro Okumura; Jun Tateishi; Junichi Yoshida; Masahiro Seo; Masamichi Yano; Takaharu Hayashi; Yusuke Nakagawa; Shunsuke Tamaki; Takahisa Yamada; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Although potential therapeutic candidates for heart failure with preserved ejection fraction (HFpEF) are emerging, it is still unclear whether they will be effective in patients with left ventricular ejection fraction (LVEF) of 60% or higher. Our aim was to identify the clinical characteristics of these patients with HFpEF by comparing them to patients with LVEF below 60%. Methods and Results From a multicenter, prospective, observational cohort (PURSUIT‐HFpEF [Prospective Multicenter Obsevational Study of Patients with Heart Failure with Preserved Ejection Fraction]), we investigated 812 consecutive patients (median age, 83 years; 57% women), including 316 with 50% ≤ LVEF <60% and 496 with 60% ≤ LVEF, and compared the clinical backgrounds of the 2 groups and their prognoses for cardiac mortality or HF readmission. Two hundred four adverse outcomes occurred at a median of 366 days. Multivariable Cox regression tests adjusted for age, sex, heart rate, atrial fibrillation, estimated glomerular filtration rate, N‐terminal pro‐B‐type natriuretic peptide, and prior heart failure hospitalization revealed that systolic blood pressure (hazard ratio [HR], 0.925 [95% CI, 0.862–0.992]; P=0.028), high‐density lipoprotein to C‐reactive protein ratio (HR, 0.975 [95% CI, 0.944–0.995]; P=0.007), and left ventricular end‐diastolic volume index (HR, 0.870 [95% CI, 0.759–0.997]; P=0.037) were uniquely associated with outcomes among patients with 50% ≤ LVEF <60%, whereas only the ratio of peak early mitral inflow velocity to velocity of mitral annulus early diastolic motion e′(HR, 1.034 [95% CI, 1.003–1.062]; P=0.034) was associated with outcomes among patients with 60% ≤ LVEF. Conclusions Prognostic factors show distinct differences between patients with HFpEF with 50% ≤ LVEF <60% and with 60% ≤ LVEF. These findings suggest that the 2 groups have different inherent pathophysiology. Registration URL: https://upload.umin.ac.jp/cgi‐open‐bin/ctr_e/ctr_view.cgi?recptno=R000024414; Unique identifier: UMIN000021831 PURSUIT‐HFpEF.